Teacher Identity Development in Professional Learning: An Overview of Theoretical Frameworks - Ahmad, Hussain; Shah, Sayyed Rashid; Fatmawati, Latada; Muhammad Nubli, Abdul Wahab (Rafaad, 2019)
This article discusses the need and essential components of theoretical frameworks and elaborates on the most notable theories that may be employed in the process of conceptualizing teacher identity development in different professional learning experiences. First of all, it explains the significance of including a theoretical framework and identifies various factors that researchers might consider for establishing a justifiable theoretical base for their research studies. Introducing the construct of teacher identity and its various attributes, the article then goes on to present seven theories that might influence the construction of teacher identity teacher learning in an educational setting. Hence the article explicates how educational researchers should take into consideration the theoretical underpinnings of Wenger’s Communities of Practice (CoP), Vygotsky’s Socio-cultural Theory, Activity Theory, Positioning Theory, Cultural Production and Practice Theory, Dialogical Self-theory, and/or The Dynamic System Model of Role Identity (DSMRI) in order to show their philosophical, epistemological, methodological, and analytical approach to research studies in the realm of teacher identity. At the end, the article suggests some practical steps on implementing one or more theories and conceptualizing teacher identity in educational research.